Humic Substances Contribute to Plant Iron Nutrition Acting as Chelators and Biostimulants - Zanin, Laura; Tomasi, Nicola; Cesco, Stefano; Varanini, Zeno; Pinton, Roberto (Frontiers in Plant Science, 2019)
Improvement of plant iron nutrition as a consequence of metal complexation by humic substances (HS) extracted from different sources has been widely reported. The presence of humified fractions of the organic matter in soil sediments and solutions would contribute, depending on the solubility and the molecular size of HS, to build up a reservoir of Fe available for plants which exude metal ligands and to provide Fe-HS complexes directly usable by plant Fe uptake mechanisms. It has also been shown that HS can promote the physiological mechanisms involved in Fe acquisition acting at the transcriptional and post-transcriptional level. Furthermore, the distribution and allocation of Fe within the plant could be modified when plants were supplied with water soluble Fe-HS complexes as compared with other natural or synthetic chelates. These effects are in line with previous observations showing that treatments with HS were able to induce changes in root morphology and modulate plant membrane activities related to nutrient acquisition, pathways of primary and secondary metabolism, hormonal and reactive oxygen balance. The multifaceted action of HS indicates that soluble Fe-HS complexes, either naturally present in the soil or exogenously supplied to the plants, can promote Fe acquisition in a complex way by providing a readily available iron form in the rhizosphere and by directly affecting plant physiology. Furthermore, the possibility to use Fe-HS of different sources, size and solubility may be considered as an environmental-friendly tool for Fe fertilization of crops.